Case Report: New phenotype of late-onset Stüve-Wiedemann syndrome due to a C-terminal variant in the LIFR gene - Evgenia Melnik; Margarita Sharova; Vladimir Kenis; Anna Morgul; Viktoria Zabnenkova; Tatiana Markova (Frontiers Media S.A., 2024)
An early diagnosis of Stüve-Wiedemann syndrome is crucial due to its high neonatal lethality and the potential for autonomic dysfunction in children. Herein, we describe a patient with a late-onset, arthrogryposis-like phenotype form of Stüve-Wiedemann syndrome. While most cases result in neonatal complications, our patient only presented with camptodactyly, ulnar deviation of the wrist, and minor facial features at birth, resembling an arthrogryposis-like phenotype. The condition went undiagnosed until adolescence when noticeable gait and posture abnormalities emerged. Clinical and radiological findings confirmed the diagnosis of benign Stüve-Wiedemann syndrome with light autonomic dysregulation. Notably, our patient lacked the typical bent bone features but showed widened metaphyses and thickened femoral necks. Genetic analysis revealed a novel variant in the last exon of the LIFR gene, possibly explaining the mild phenotype. This case expands our understanding of Stüve-Wiedemann syndrome variability, aiding in earlier detection and better medical-genetic counseling.